TRANSFORMASI PESANTREN MENGHADAPI ERA REVOLUSI DIGITAL 4.0 - Ridwan Maulana Rifqi Muzakky; Rijaal Mahmuudy; Andhita Risko Faristiana (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The transformation of pesantren students in the digital era 4.0 is a significant challenge for traditional Islamic educational institutions. This article aims to explain the concept of pesantren in the digital era, the challenges faced, the opportunities that exist, and best practices in facing this transformation. Pesantren has undergone important changes in the digital era 4.0. The introduction of this article provides an introduction to pesantren and summarizes the changes in the digital age. The second part explains the concept of pesantren in the digital era 4.0, including the definition and characteristics of traditional pesantren as well as the concept of digital pesantren that integrate technology in Islamic education. This transformation brings challenges for pesantren students, including the rapid digital revolution, limited technological infrastructure, and anxiety about the negative impact of technology on students. However, this article also reveals opportunities, such as increased access to information and online learning, the use of technology to expand student networks, and adaptive curriculum development. The next section presents some best practices in the transformation of pesantren students. Case studies of pesantren that successfully integrate technology are presented as examples, as well as the importance of the role of educators and pesantren support. Collaboration with educational institutions and the technology industry is also considered important. Challenges in this transformation include changing the paradigm and culture of pesantren, as well as the need for training and capacity building for teachers and students. The development of technological infrastructure is the focus of this transformation. This article concludes that the transformation of pesantren students in the digital era 4.0 is very important. Pesantren need to adapt and innovate as part of the digital revolution. The future view of pesantren emphasizes the importance of adaptation and innovation in facing challenges and taking advantage of the opportunities offered by the digital era 4.0.